Pengaruh Product Quality, Service Quality terhadap Customer Loyalty Ayam Geprek Goldchick yang dimediasi oleh Customer Satisfaction - Isnaini Nuzula Agustin; Lily Purwianti; Tasya Gebee Hasvia; Nevi Ariyu De Utami; Gita Aulia; Joy Happy Jones (Pascasarjana STIE Amkop Makassar, 2023)
Penelitian ini dilakukan untuk menganalisa pengaruh dari Product Quality dan Service Quality terhadap Customer loyalty pada Ayam Geprek Goldchick yang dimediasi oleh Customer Satisfaction. Data yang dikumpulkan terdiri dari data primer dan data sekunder. Data primer diperoleh melalui penyebaran kuesioner dalam bentuk google form dan terkumpul sebanyak 218 Responden. Peneliti membagikan kuesioner kepada masyarakat Kota Batam yang pernah membeli produk Ayam Geprek Goldchick. Pengujian penelitian ini menggunakan alat analisis SmartPls. Hasil penelitian menunjukkan bahwa Product Quality dan Service Quality memiliki hubungan yang positif signifikan terhadap Customer Satisfaction. Product Quality dan Customer Satisfaction memiliki hubungan yang positif signifikan terhadap Customer Loyalty. Sedangkan Service Quality tidak berpengaruh signifikan terhadap Customer Loyalty. Terdapat hubungan mediasi oleh Customer Satisfaction pada Product Quality terhadap Customer Loyalty, dan terdapat hubungan mediasi oleh Customer Satisfaction pada Service Quality terhadap Customer Loyalty.Â Kata Kunci: Product Quality, Service Quality, Customer Loyalty, Customer Satisfaction, Ayam Geprek.Â AbstractThis research was conducted to analyze the influence of Product Quality and Service Quality on Customer Loyalty in Geprek Goldchick Chicken mediated by Customer Satisfaction. The data collected consists of primary data and secondary data. Primary data was obtained through distributing questionnaires in the form of a google form and collected as many as 218 respondents. Researchers distributed questionnaires to the people of Batam City who had bought Goldchick Geprek products. Testing this research using the SmartPls analysis tool. The results of the study show that Product Quality and Service Quality have a significant positive relationship to Customer Satisfaction. Product Quality and Customer Satisfaction have a significant positive relationship to Customer Loyalty. While Service Quality has no significant effect on Customer Loyalty. There is a mediation relationship between Customer Satisfaction on Product Quality and Customer Loyalty, and there is a mediation relationship between Customer Satisfaction on Service Quality and Customer Loyalty.Â Keywords: Product Quality, Service Quality, Customer Loyalty, Customer Satisfaction, Ayam Geprek.